Eksplorasi Ogung Batak Toba Terhadap Konsep Bangun Ruang - Pandiangan, Damayanti; Tambunan, Hardi; Simanjuntak, Ruth M. (Indo-MathEdu Intellectuals Journal, 2026)
Ethnomathematics serves as a significant pedagogical approach for linking mathematical concepts with local culture, thereby making learning more contextual and meaningful. However, the utilization of cultural heritage as a resource for mathematics education remains limited; this includes the Ogung—a traditional musical instrument of the Toba Batak people—which holds the potential to embody various geometric concepts. This study aims to explore the 3D geometric concepts found in the Toba Batak Ogung as an application of ethnomathematics in mathematics education. A qualitative approach employing an exploratory method was used. Data were gathered through observation, interviews with Toba Batak artisans and cultural practitioners, and documentation within the Toba Batak cultural region; the data were subsequently analyzed descriptively through data reduction, data presentation, and conclusion drawing. The results indicate that the body of the Ogung represents a cylinder, the pencu (central boss) resembles a hemisphere, and the top and bottom surfaces are circular. Furthermore, concepts such as radius, diameter, height, surface area, and volume were identified. This study contributes to enriching the field of ethnomathematics by demonstrating that the Toba Batak Ogung can serve as a contextual learning resource, helping students understand 3D geometric concepts while simultaneously supporting the preservation of local culture.